Change in mutation patterns of Plasmodium vivax dihydrofolate reductase (Pvdhfr) and dihydropteroate synthase (Pvdhps) in P. vivax isolates from malaria endemic areas of Thailand - Jiraporn Kuesap; Kanchana Rungsrihirunrat; Pimwan Thongdee; Ronnatrai Ruangweerayut; Kesara Na-Bangchang (Memorias do Instituto Oswaldo Cruz, 2011)
Malaria is the most important public health problem in several countries. In Thailand, co-infections of Plasmodium vivax and Plasmodium falciparum are common. We examined the prevalence and patterns of mutations in P. vivax dihydrofolate reductase (Pvdhfr) and P. vivax dihydropteroate synthase (Pvdhps) in 103 blood samples collected from patients with P. vivax infection who had attended the malaria clinic in Mae Sot, Tak Province during 2009 and 2010. Using nested polymerase chain reaction-restriction fragment length polymorfism, we examined single nucleotide polymorphisms-haplotypes at amino acid positions 13, 33, 57, 58, 61, 117 and 173 of Pvdhfr and 383 and 553 of Pvdhps. All parasite isolates carried mutant Pvdhfr alleles, of which the most common alleles were triple mutants (99%). Eight different types of Pvdhfr and combination alleles were found, as follows: 57I/58R/117T, 57I/58R/117T, 57I/58R/117T/N, 57L/58R/117T, 57L/58R/117T, 58R/61M/117N, 58R/61M/117N and 13L/57L/58R/117T. The most common Pvdhfr alleles were 57I/58R/117T (77.7%), 57I/58R/117T/N (1%), 57L/58R/117T (5.8%) and 58R/61M/117N (14.5%). The most common Pvdhfr alleles were 57I/58R/117T (77.7%), 57I/58R/117T/N (1%), 57L/58R/117T (5.8%) and 58R/61M/117N (14.5%). Additionally, we recovered one isolate of a carrying a quadruple mutant allele, 13L/57L/58R/117T. The most prevalent Pvdhps allele was a single mutation in amino acid 383 (82.5%), followed by the wild-type A383/A553 (17.5%) allele. Results suggest that all P. vivax isolates in Thailand carry some combination of mutations in Pvdhfr and Pvdhps. Our findings demonstrate that development of new antifolate drugs effective against sulfadoxine-pyrimethamine-resistant P. vivax is required.